1993
DOI: 10.1210/endo.132.1.8419125
|View full text |Cite
|
Sign up to set email alerts
|

Loss of lutropin/human choriogonadotropin receptor messenger ribonucleic acid during ligand-induced down-regulation occurs post transcriptionally.

Abstract: Previous studies have demonstrated that ligand-induced down-regulation of the LH/hCG receptor in rat corpus luteum results in a loss of ligand-binding activity and a parallel decline in steady state levels of receptor mRNA. The purpose of the present study was to determine whether this loss of receptor mRNA during receptor down-regulation is due to inhibition of transcription or increased degradation of the receptor mRNA. To differentiate between these two possibilities, nuclear run-off assays were performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
35
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 20 publications
3
35
0
Order By: Relevance
“…We have shown that the decline in cell surface LHR expression seen after hCG administration is paralleled by a specific loss of all four LHR mRNA transcripts (6.7, 4.4, 2.6, and 1.8 kb) in the ovary (9). Furthermore, the loss of LHR mRNA does not result from decreased transcription but occurs post-transcriptionally with a 3-fold decrease in half-life (8).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…We have shown that the decline in cell surface LHR expression seen after hCG administration is paralleled by a specific loss of all four LHR mRNA transcripts (6.7, 4.4, 2.6, and 1.8 kb) in the ovary (9). Furthermore, the loss of LHR mRNA does not result from decreased transcription but occurs post-transcriptionally with a 3-fold decrease in half-life (8).…”
mentioning
confidence: 87%
“…The cell surface expression of LHR varies during different stages of the ovarian cycle. Its expression in granulosa cells and luteal cells is greatly decreased by an endogenous preovulatory LH surge or by the administration of a pharmacological dose of human chorionic gonadotropin (hCG), a placental counterpart of LH (5)(6)(7)(8). We have shown that the decline in cell surface LHR expression seen after hCG administration is paralleled by a specific loss of all four LHR mRNA transcripts (6.7, 4.4, 2.6, and 1.8 kb) in the ovary (9).…”
mentioning
confidence: 99%
“…The loss of LH receptor mRNA occured through post-transcriptional mechanisms as the transcription rate, determined by nuclear run on assays, remained identical in hCG treated group compared to the control. In fact, the nuclei isolated from the hCG treated ovaries was found to incorporate 3 H uridine into total RNA at much higher levels than that seen in control ovaries (Lu, et al 1993). Thus, we concluded that the loss of steady state LH receptor mRNA seen in the hCG treated group was due to increased mRNA degradation rather than a decrease in the rate of its synthesis.…”
Section: Lh Receptor Mrna Expression During Ligand-induced Down-regulmentioning
confidence: 65%
“…Previous studies have shown that in the rat, preovulatory LH surge produces a rapid decline in LH receptor expression as well as an uncoupling of LH receptor from the cognate G proteins (Hoffman, et al 1991, Lapolt, et al 1990, Lu, et al 1993. The loss of LH receptor from the cell surface may be explained on the basis of the rapid endocytosis of the LH-receptor complex, causing its depletion.…”
Section: Lh Receptor Mrna Expression During Ligand-induced Down-regulmentioning
confidence: 99%
See 1 more Smart Citation